Sistem Web Real Time untuk Pelacakan Lokasi Pedagang Keliling - Raka Akbar Hartolo; Febi Eka Febriansyah; Irwan Adi Pribadi; Favorisen Rosyking Lumbanraja (Jurnal Pepadun, 2023)
The rapid progress in technology, particularly in the realm of information technology, has significantly impacted various aspects of daily life. Despite these advancements, many street vendors continue to conduct trade within housing complexes or on smaller streets. This presents a challenge for potential buyers who find it inconvenient to purchase goods from street vendors due to uncertainties about their presence and the types of merchandise they offer. To address this issue, a viable solution is proposed: the development of a tracking system that utilizes GPS technology on smartphones to monitor the movements of street vendors. The location data of these vendors is transmitted to the internet, where it is converted into accessible information through a web interface built with the Codeigniter framework. Black Box testing confirms the effective functionality of the system, and the evaluation yields a score of 82.28%, indicating its successful implementation.